Demand on home furniture in Courts Mammoth Temerloh Branch / Muhammad Nizam Jamaludin and Abdul Jalil Ahmad - Jamaludin, Muhammad Nizam; Ahmad, Abdul Jalil (2011)
The study carried out was intended to find out the demand of home furniture based on sales made by Courts Mammoth in Temerloh. The study focused on three main home furniture items which includes; coffee table, sofa, and dining table sold in Courts Mammoth that is located in Temerloh, Pahang. From the data that was collected and analyzed, it was observed that almost the entire product range showed the same sale trend that is high sale volume in August and gradually reduced towards the end of the year. It is due to the economic condition and the lifestyle of the residents of Temerloh and nearby districts.